PERAN KADER PEMBERDAYAAN KESEJAHTERAAN KELUARGA (PKK) DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DI POSYANDU BUNGUR KELURAHAN SEMPER BARAT JAKARTA UTARA - Rahmadanti, Bunga; Sari Dewi, Ratnah; Melia, Ika Rizqy (UNIB Press, 2023)
Abstract: The research objectives (1) describe the role of PKK cadres in increasing community participation, (2) describe the factors that influence community participation. The research used a descriptive qualitative approach with the research subjects including the chairperson and two members of the PKK posyandu cadres, as well as three community participants. The research data were collected through interviews, observation, and documentation. The results showed that (1) the role of PKK cadres as facilitators, motivators, planners, implementers, and instructors has been running well. (2) Factors influencing community participation include education level, where people with higher education tend to be more critical and active in the implementation of posyandu. Information and communication are also influential, where good communication allows communities to access information about posyandu schedules, services provided, and the benefits they obtain. The activeness of the facilitator can provide motivation and support to the community to actively participate in posyandu. Keyword : Role, Family Welfare Empowerment, Community Participation